Examining the Relationship between Engineering Mathematics Performance and Core Engineering Courses at the University of Guyana - Basheer Khan; Elena Trim; Safrawz Sharief; Shawn Jagnandan; Antalov Jagnandan; Andrunie Harris (Engineering Research: Perspectives on Recent Advances Vol. 1, 2024)
Over the last decade, administrators and lecturers at the University of Guyana, Faculty of Engineering and Technology have voiced their concerns about the low performances in Engineering Mathematics courses in the Associate of Science and Bachelor of Science programs. It is widely believed by lecturers and professors in engineering that to complete a bachelor’s of engineering or a bachelor’s of science degree, students must excel in Engineering Mathematics at the University level. The notion is that students who grasp Engineering Mathematics concepts, theory, and application to engineering disciplines such as Mechanical and Civil, should translate to a strong performance in engineering core calculation courses. Currently, there is limited research that can validate this assumption. Students who completed their Mechanical and Civil Engineering Bachelor’s degree in 2024 had their academic profile analyzed to determine the relationship between their performance in Engineering Mathematics year 3 which is year 1 of the bachelor’s since at the University of Guyana, the Engineering program is a 2+2, 2 years for the Associate degree and another 2 years for the bachelor’s degree. Their Engineering Mathematics grades and scores were correlated with performances in core calculation courses in Mechanical Engineering such as Applied Thermodynamics, Theory of Machines and Strength of Materials, and Civil Engineering Course Structural Analysis. All the courses are in semester 1 in year 3. The quantitative methodology design was utilised for this study. Secondary data was used since it was graduating students’ academic profiles that were studied, which means that the data existed and was gathered from secondary sources. The Spearman’s rank correlation coefficient showed that there is a moderate positive correlation of R=0.55 between Engineering Mathematics (EMT 3100) performance/grade and Strength of Materials (MEC 3108) performance/grade for Mechanical Engineering. The R=0.55 statistic suggests that there is a moderate relationship between EMT 3100 and MEC 3108 performances, which means that students who perform excellently in engineering mathematics will also perform excellent in strength of materials. However, the Theory of Machines (MEC 3107) and Applied Thermodynamics (MEC 3106) when analyzed with EMT 3100, revealed no correlation. Furthermore, there is a weak negative correlation between EMT 3100 and Structural Analysis (CIV 3115).